First record of the genus Zaglyptus Förster (Hymenoptera: Ichneumonidae: Pimplinae) from Vietnam, with description of one new species - Pham, Nhi Thi (Zootaxa, 2013)
The ichneumonid wasp genus Zaglyptus Förster, 1868 is reported for the first time from Vietnam, with three species found in the country. One new species, Zaglyptus guptai sp. nov., is described based on material collected in Chu Yang Sin NP, Dak Lak Province. Two other species, Z. glaber Gupta and Z. nigrolineatus, Gupta are recorded as new for the country. In addition, the subspecies Z. glaber singaporensis Gupta is synonymised with the nominate subspecies.